An Autologously Generated Platelet-Rich Plasma Suturable Membrane May Enhance Peripheral Nerve Regeneration after Neurorraphy in an Acute Injury Model of Sciatic Nerve Neurotmesis - Giannessi, Elisabetta; Coli, Alessandra; Stornelli, Maria Rita; Miragliotta, Vincenzo; Pirone, Andrea; Lenzi, Carla; Burchielli, Silvia; Vozzi, Giovanni; De Maria, Carmelo; Giorgetti, Margherita (Journal of Reconstructive Microsurgery, 2014)
Background The aim of this study was to investigate the ability of suturable platelet-rich plasma (PRP) membrane to promote peripheral nerve regeneration after neurotmesis and neurorraphy.Methods A total of 36 rats were used: 32 animals underwent surgery and were split in two groups. An interim sacrifice was performed at 6 weeks postsurgery and final sacrifice at 12 weeks; four animals did not sustain nerve injury and served as control. Clinical, electromyographic (EMG), gross, and histological changes were assessed. The EMG signal was evaluated for its amplitude and frequency spectrum. Number of regenerating fibers, their diameter, and myelin thickness were histologically analyzed.Results Both EMG parameters showed a significant (p < 0.05) effect of treatment at 6 and 12 weeks postsurgery. At 6 weeks, the fiber density was statistically different between treated and untreated animals with a higher observed density in treated nerves. No difference in fiber density was observed at 12 weeks postsurgery. The distribution of fiber diameters showed an effect at 12 weeks when only the sections of the nerves sutured with PRP showed fibers with diameters greater than 6 µm.Discussion Our data show that the application of a PRP fibrin membrane around the neurorraphy improves the nerve regeneration process in a rat sciatic nerve model. The use of PRP as a suturable membrane could perform an action not only as a source of bioactive proteins but also as a nerve guide to hold the scar reaction and thus improve axonal regeneration.
Keywords: platelet-rich plasma; peripheral nerve surgery; sciatic nerve; electromyography; histology; rat